If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (x + -50) Reorder the terms: x = (-50 + x) Remove parenthesis around (-50 + x) x = -50 + x Add '-1x' to each side of the equation. x + -1x = -50 + x + -1x Combine like terms: x + -1x = 0 0 = -50 + x + -1x Combine like terms: x + -1x = 0 0 = -50 + 0 0 = -50 Solving 0 = -50 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x^2+kx+2=0 | | 10k=12-8K | | 11x+14= | | 9x^2-4y^2-18x-24y-27=0 | | 4(x-6)x=5(x-7)+11 | | 8(x+7)+8=8x+3 | | W+(-1)=16 | | 15x-6x=8x | | 12(n-2)=3(8+4n) | | -18+24-18+(-6)= | | (38.14)(0.002)= | | |x|=-4 | | 16=3s-4(24-s) | | (6.3)(5.7)= | | y=-0.60(55)+114 | | y=-0.60(45)+114 | | 2x+1=-19 | | X(3-7)=-4x | | y=-0.60(35)+114 | | y=-0.60(25)+114 | | 2x+x-8=5(2x-3) | | (2x+3)(x-7)=4(x-7) | | y=5x+18 | | 15x-39=-4 | | 3(2x-3)=4x | | y=3(3) | | 7(t-6)+5t=6(2t+4)-9 | | 9w^2+42w+49=0 | | -(4y+2)-(-3y-6)=-4 | | 6b^2+35b-6=0 | | 23x^2-7x=0 | | p=s-20 |